An investigation on the effects of organizational memory and human capital on innovation and absorptive capacity - Zahra Mansouri; Touran Razmavar; Mohamad Reza Nour Ali (Management Science Letters)
Innovation is considered as an enabling tool for creating value and sustainable competitive advantage for organizations in dynamic environment of our times along with its ever-increasing complexities. Until innovation in developing countries needs more capital and talent, human capital (HC) is a key factor in innovative performance. People are the most important factor of exploitation of foreign knowledge; and knowledge focus in business environment is highly dependent on external information sources in order to develop innovation and improve performance of the company. Studies have shown that although importance level of knowledge is increased, but only 30 percent of existing knowledge is being used in organizations. Expensive but evitable mistakes take place due to information blockage; and the risk of losing knowledge is exceptionally higher when people leave the organization. This study is among the field research. The population includes large manufacturing firms across Khuzestan Province having been active throughout 2013. The data collection tool was a structured questionnaire and sampling is convenience method. The research questionnaire was distributed among a sample of 331 R&D and Human resources Experts selected using simple random sampling. The collected data were analyzed using SPSS and Amos statistical programs. The results indicate that organizational memory had significant impact on ACAP and innovation. Results also showed a significant positive effect of HC on ACAP, but did not support the effect of HC on innovation.